Spontaneous clearance of a dislodged root in the maxillary antrum. (18th January 2018) - Tocaciu, S.; Sillifant, P.
Abstract: Dislodgement of maxillary tooth roots into the adjacent maxillary antrum is an unpleasant experience for both the patient and the operator. In the majority of cases, these roots need to be removed from the sinus to avoid further complications such as infection and oroantral fistula formation. A case is described where a dislodged root successfully migrated from the apex of the tooth socket to the ostium of the maxillary antrum via the function of the respiratory epithelium's 'mucociliary escalator'. The indications and contra‐indications for sinus exploration and root retrieval are discussed, and a treatment algorithm is proposed to include cases where monitoring for spontaneous exfoliation may be included.